Dampak Retribusi Jasa Umum Terhadap Pendapatan Asli Daerah Kabupaten Kuningan - Umam, Khaerul; Fadila, Yendri Iqbal (Department of Public Administration, 2019)
The target for public service levies is high every year but revenue realization is still far from the target. This shows the existence of fluctuations in revenue from general service levies on Kuningan's own-source revenue (PAD). This study aims to analyze the effect of public service levies on the original income of Kuningan Regency. The research approach used in this study is quantitative with an associative type of research. This research employed saturated sampling types. Techniques from data collection efforts were obtained through field research and library research. Based on the results of the hypothesis test, it appears that public service fees have a positive effect, amounting to 0.514 for an increase in local own-source revenue and in the quite high category. This means that between public service levies and local own-source revenue (PAD) have a fairly high (positive) relationship. If public service levies are higher, it will be followed by higher local own-source revenues.